Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/ner.12980
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Temperature Increases by a 10 kHz Spinal Cord Stimulation System: Phantom and Bioheat Model

Abstract: Objective: A recently introduced Spinal Cord Stimulation (SCS) system operates at 10 kHz, faster than conventional SCS systems, resulting in significantly more power delivered to tissues. Using a SCS heat phantom and bioheat multi-physics model, we characterized tissue temperature increases by this 10 kHz system. We also evaluated its Implanted Pulse Generator (IPG) output compliance and the role of impedance in temperature increases. Materials and Methods:The 10 kHz SCS system output was characterized under r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
0
22
2
Order By: Relevance
“…10,11,29,33,34 Durable and differentiated outcomes seen with 10 kHz SCS treatment may be attributed to its unique mechanism of action. [35][36][37][38][39][40][41][42] Using in vivo and ex vivo electrophysiological approaches, Lee et al reported that unlike low-intensity (sub-sensory threshold) 1 kHz and 5 kHz SCS, 10 kHz SCS selectively activated inhibitory interneurons in the spinal dorsal horn (DH) and proposed that low-intensity 10 kHz SCS provided paresthesia-free pain relief possibly by activating the inhibitory interneurons without activating dorsal column fibers. 35 Researchers from Chang Gung Memorial Hospital, Taiwan used spared nerve injury…”
mentioning
confidence: 99%
“…10,11,29,33,34 Durable and differentiated outcomes seen with 10 kHz SCS treatment may be attributed to its unique mechanism of action. [35][36][37][38][39][40][41][42] Using in vivo and ex vivo electrophysiological approaches, Lee et al reported that unlike low-intensity (sub-sensory threshold) 1 kHz and 5 kHz SCS, 10 kHz SCS selectively activated inhibitory interneurons in the spinal dorsal horn (DH) and proposed that low-intensity 10 kHz SCS provided paresthesia-free pain relief possibly by activating the inhibitory interneurons without activating dorsal column fibers. 35 Researchers from Chang Gung Memorial Hospital, Taiwan used spared nerve injury…”
mentioning
confidence: 99%
“…The biophysics of heating are analogous experimentally verified prior simulations of conventional rate DBS and kHz SCS , however comparisons highlight the importance of stimulation dose (electrodes and waveform) as well as tissue anatomy and parameters. Compared to monopolar stimulation, energizing an adjacent contact in a bipolar electrode configuration may further increase temperature .…”
Section: Discussionmentioning
confidence: 63%
“…Static RMS values were applied (Eqn. (3)) for tested clinical kHz‐DBS intensities (3‐7 mA peak at 30 μs and 10 kHz), and this approach was supported by prior phantom verification for conventional DBS and kHz‐SCS . IRMS=1emIPeakt*f=IPeakD where I RMS is the corresponding RMS value of peak stimulation intensity ( I peak ), t is the combined (anodic and cathodic phase) pulse width, f is the frequency, and D is the duty cycle.…”
Section: Methodsmentioning
confidence: 78%
“…Impedance is also directly proportional to the energy consumption of the IPG, thus making it also proportional to the battery life of the device itself [8]. However, more recently this theory has been challenged to suggest there is an inverse relationship between impedance and the energy: E = (V2 9 pulse width 9 f)/R [9]. SCS systems are unable to transition to MRI-conditional modes in states of high impedance, as interactions generated by the MRI machine can [10].…”
Section: Discussionmentioning
confidence: 99%
“…Lead fracture was one of the drivers behind long-term failure rates of 5.9%, some diagnosed by routine impedance testing [9] North et al…”
Section: Lead Fracturementioning
confidence: 99%